Crystal growth and spin reorientation transition in Sm0.4Er0.6FeO3 orthoferrite. (April 2016) - Zhao, Xiangyang; Zhang, Kailin; Xu, Kai; Man, Peiwen; Xie, Tao; Wu, Anhua; Ma, Guohong; Cao, Shixun; Su, Liangbi
Abstract: High quality Sm0.4 Er0.6 FeO3 single crystal has been successfully grown by the floating zone method. Temperature dependence of the magnetizations of Sm0.4 Er0.6 FeO3 under ZFC process is studied in the temperature range of 4–300 K. Spin reorientation transition between Γ 2 (Gz, Fx) and Γ 4 (Gx, Fz) is observed in the temperature range of 170–210 K, which is significantly lower than that of SmFeO3, while much higher than that of ErFeO3 . A compensation point (35.8 K) corresponding to zero magnetization and a spontaneous magnetization reversal transition at 49.5 K are observed in Sm0.4 Er0.6 FeO3 . Temperature-induced SRT of Sm0.4 Er0.6 FeO3 is systematically studied by THz-TDS range from 40 K to 300 K. The temperature dependence of amplitude of AFM mode coincides well with the magnetization measurement which demonstrate that SRT in Sm0.4 Er0.6 FeO3 can be studied through the amplitude of AFM mode FID emission. The AF mode frequency is almost invariant, while the F mode frequency significantly decreases with increasing temperature, which could be explained by the temperature dependence of anisotropy energy. Highlights: SRT of Sm0.4 Er0.6 FeO3 is observed in the temperature range of 170–210 K. A compensation point and a spontaneous spin-flip transition are observed. Temperature-induced SRT is systematically studied by THz-TDS.